Cashew (Anacardium occidentale) Nut-Shell Liquid as Antioxidant in Bulk Soybean Oil - Sandra-Yaneth Gaitán-Jiménez; Luz-Patricia Restrepo-Sánchez; Fabián Parada-Alfonso; Carlos-Eduardo Narváez-Cuenca (Molecules, 2022)
Recently, natural antioxidants for the food industry have become an important focus. Cashew nut-shell liquid (CNSL) is composed of compounds that can act as natural antioxidants in food systems. The aim of this work was to evaluate the potential of CNSL and its components to act as natural antioxidants in a bulk oil system. CNSL was treated with calcium hydroxide to obtain two fractions [cardol/cardanols acid fraction (CCF) and anacardic acid fraction (AF)]. CNSL, FF and AF were analyzed by thin-layer chromatography and Fourier-transform infrared spectroscopy. The protective effects of CNSL, CCF and AF were tested in terms of the peroxide value of bulk soybean oil in accelerated assays and were compared against controls with and without synthetic antioxidants (CSA and CWA). CNLS, CCF, AF and CSA were tested at 200 mg/kg soybean oil by incubation at 30, 40, 50 and 60 °C for five days. The activation energy (Ea) for the production of peroxides was calculated by using the linearized Arrhenius equation. Thin-layer chromatography and Fourier-transform infrared spectroscopy revealed that (i) CNSL contained cardanols, anacardic acids, and cardols; (ii) CCF contained cardanols and cardols; and (iii) AF contained anacardic acids. CSA (Ea 35,355 J/mol) was the most effective antioxidant, followed by CCF (Ea 31,498 J/mol) and by CNSL (Ea 26,351 J/mol). AF exhibited pro-oxidant activity (Ea 8339 J/mol) compared with that of CWA (Ea 15,684 J/mol). Therefore, cardols and cardanols from CNSL can be used as a natural antioxidant in soybean oil.